The prevalence and risk factors of allergic and respiratory symptoms in a regional cohort of extremely low birth weight children (<1000 g) - Kwinta Przemko; Lis Grzegorz; Klimek Malgorzata; Grudzien Andrzej; Tomasik Tomasz; Poplawska Karolina; Pietrzyk Jacek Jozef (BMC, 2013)
Abstract Background Children who were <1000 g (ELBW extremely low birth weight) at birth more frequently present with wheezing which is the most common reason that pediatric consultation is sought. Therefore asthma is diagnosed very often. However is the asthma that is diagnosed in ELBW subjects atopic in origin, or is there a different etiology? Aim To determine if ELBW infants are at higher risk for the development of allergic and respiratory symptoms and to establish if there were any specific risk factors for these symptoms. Methods 81 children born with a mean birthweight of 845 g (91% of available cohort) were evaluated at the mean age 6.7 years. The control group included 40 full-term children. The children were examined for clinical signs of allergy, and were subjected to the following tests: serum total IgE, skin prick tests (SPT), exhaled nitric oxide measurement (FeNO) and spirometry. Results ELBW children had wheezing episodes more often (64% vs. 25%; OR (odds ratio): 5.38; 95% CI (confidence interval): 2.14-13.8) and were diagnosed more frequently with asthma (32% vs. 7.5%; OR: 5.83, 95% CI: 1.52-26) than their term born peers. The most important risk factors for wheezing persistence were hospitalization and wheezing episodes in first 24 months of life. Mean serum tIgE level (geometric mean: 32+/−4 vs. 56+/−4 kU/L; p=0.002) was higher and the number of children with positive results of tIgE level (12% vs. 32%; p=0.02) were more frequent in the control group. Children from the control group also more frequently had SPT, however this data was not statistically significant (11% vs. 24%; p=0.09). All of the ELBW had normal FeNO level (<=20 ppb), but 5 children from the control group had abnormal results (p=0.02). There was no difference between the groups in the occurrence of allergic symptoms. Conclusion ELBW children have more frequent respiratory, but not allergic problems at the age of 6-7 years compared to children born at term. The need for rehospitalization in the first 2 years of life, was a more important risk factor of future respiratory problems at the age of 7 than perinatal factors, the diagnosis of bronchopulmonary dysplasia or allergy.